2019
DOI: 10.2478/jomb-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Association of overweight and obesity with cardiovascular risk factors in patients with atherosclerotic diseases

Abstract: Summary Background The aim of this study was to compare demographic, clinical and biochemical characteristics, including inflammatory markers, according to the nutritional status of patients with verified atherosclerotic disease. Methods This cross-sectional study involved 1045 consecutive patients with verified carotid disease or peripheral arterial disease (PAD). Anthropometric parameters and data on cardiovascular risk factors and therapy for hypertension and hyperlipidemia were collected for all partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Adolescence, as a period of increased nutritional demand and changes in psychosocial behavior, is often accompanied with obesity and metabolic disturbances tightly related to insulin resistance (IR) [1]. IR may precede other cardiometabolic disorders, such as nonalcoholic fatty liver disease, metabolic syndrome, type 2 diabetes, and cardiovascular disease later in life [2][3][4][5]. In the aim of better recognition of the regulatory mechanisms of insulin signaling pathways, many biomolecules and their mutual interaction have been investigated so far [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence, as a period of increased nutritional demand and changes in psychosocial behavior, is often accompanied with obesity and metabolic disturbances tightly related to insulin resistance (IR) [1]. IR may precede other cardiometabolic disorders, such as nonalcoholic fatty liver disease, metabolic syndrome, type 2 diabetes, and cardiovascular disease later in life [2][3][4][5]. In the aim of better recognition of the regulatory mechanisms of insulin signaling pathways, many biomolecules and their mutual interaction have been investigated so far [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…All of these metabolic disturbances may lead to increased ALT and GGT activity, and to a decreased bilirubin level [6,25]. Moreover, not only do high levels of free fatty acids in addition to insulin resistance lead to hepatocytes dysfunction, but they also promote endothelial dysfunction, reduce production of nitric oxide, vasoconstriction, and inflammation with consequent initiation and progression of atherosclerosis [29,30], thus further supporting the link between obesity, high triglycerides, and inflammation level and CVD. The limitations of this study need to be reported.…”
Section: Discussionmentioning
confidence: 94%
“…Obesity is a significant CVD risk factor and the BMI cut-off point to define obesity is 30 kg/m 2 [ 1 ]. In addition to CVD, the pre-obesity condition predisposes toward other complications, such as the risk for cancer that begins to increase at a BMI of 21 kg/m 2 , the risk for diabetes that starts to rise at 22 kg/m 2 , and the risk of musculoskeletal-related illnesses that starts to increase at 24 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%